Fixed-Point Algorithms for Energy-Efficient Power Allocation in Spectrum-Sharing Wireless Networks - Yuzhou Li; Tao Jiang (2016 IEEE Global Communications Conference (GLOBECOM), 2016)
In this paper, we investigate the fundamental energy- efficient power allocation problem in spectrum-sharing wireless networks. We introduce an energy-rate tradeoff index (EI) to characterize how efficiently the energy is consumed and formulate an optimization problem to maximize the EI subject to the power budget constraints. We first show that the EI maximization problem is intimately connected to the extensively investigated energy efficiency (EE) maximization problems. Due to the nonconvexity and NP-hardness of the formulation, we focus on designing cost-efficient and easy-implementation algorithms instead of finding globally optimal but exponential-complexity solutions. Leveraging the high signal-to-interference-plus-noise ratio (SINR) approximation method, we develop a simple fixed-point algorithm with fast convergence, fully distributed framework, and tuning-free properties. Simulation results exhibit the effectiveness of the proposed algorithm.